1974
DOI: 10.1126/science.183.4124.520
|View full text |Cite
|
Sign up to set email alerts
|

Toxaphene Insecticide: A Complex Biodegradable Mixture

Abstract: Adsorption and gas-liquid chromatography separate toxaphene into at least 175 polychlorinated 10-carbon compounds including Cl(6), Cl(7), Cl(8), Cl(9), and Cl(10) derivatives. One toxic component is 2,2,5-endo,6-exo,8,9,10-heptachlorobornane. Rats metabolically dechlorinate toxaphene, removing about half of the chlorine from the technical insecticide and from each of seven subfractions of varying composition and toxicity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
53
0

Year Published

1991
1991
2002
2002

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 98 publications
(54 citation statements)
references
References 4 publications
1
53
0
Order By: Relevance
“…Toxaphene is a complex mixture primarily consisting of chlorinated bornanes (CHBs) with an average elemental composition of C 10H10Cl8 (1)(2)(3). Prior to its ban in 1982 by the U.S. Environmental Protection Agency (1), toxaphene was the most extensively used pesticide in the United States and many parts of the world.…”
Section: Introductionmentioning
confidence: 99%
“…Toxaphene is a complex mixture primarily consisting of chlorinated bornanes (CHBs) with an average elemental composition of C 10H10Cl8 (1)(2)(3). Prior to its ban in 1982 by the U.S. Environmental Protection Agency (1), toxaphene was the most extensively used pesticide in the United States and many parts of the world.…”
Section: Introductionmentioning
confidence: 99%
“…12 In addition, individual toxaphene congeners may exhibit different toxicity. 13 Accordingly, the position and the number of the chlorine atoms on the molecule determines the magnitude and nature of biological effect. 14 Consequently, an exact assignment of the stereochemistry of the chlorine atoms on the primary carbons is necessary for correct prediction of chemical reactivity and for correct assessment of degradation or accumulation in environment.…”
Section: Introductionmentioning
confidence: 99%
“…16 have suggested that the combination of high-level ab initio optimized geometries, theoretically computed NMR chemical shifts, and experimental NMR data provides a tool that can be routinely applied for structural determinations as well as the characterization of new compounds. In this paper the gauge-including atomic orbital (GIAO) 17 method have been employed to calculate 13 C chemical shifts of the polychlorinated dihydrocamphenes 1-9 using density functional theory (DFT) at the B3LYP/6-311G* level and the HF/6-31G* optimized structures as geometry input. From the data, a linear correlation between experimental and theoretical shifts has been derived.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations